Membrane Stress Caused by Unprocessed Outer Membrane Lipoprotein Intermediate Pro-Lpp Affects DnaA and Fis-Dependent Growth - Patil, Digvijay; Xun, Dan; Schueritz, Markus; Bansal, Shivani; Cheema, Amrita; Crooke, Elliott; Saxena, Rahul (Frontiers in Microbiology, 2021)
In Escherichia coli, repression of phosphatidylglycerol synthase A gene (pgsA) lowers the levels of membrane acidic phospholipids, particularly phosphatidylglycerol (PG) causing growth-arrested phenotype. The interrupted synthesis of PG is known to be associated with concomitant reduction of chromosomal content and cell mass, in addition to accumulation of unprocessed outer membrane lipoprotein intermediate, pro-Lpp, at the inner membrane. However, whether a linkage exists between the two altered-membrane outcomes remains unknown. Previously, it has been shown that pgsA+ cells overexpressing mutant Lpp(C21G) protein have growth defects similar to those caused by the unprocessed pro-Lpp intermediate in cells lacking PG. Here we found that the ectopic expression of DnaA(L366K) or deletion of fis (encoding Factor for Inversion Stimulation) permits growth of cells that otherwise would be arrested for growth due to accumulated Lpp(C21G). The DnaA(L366K)-mediated restoration of growth occurs by reduced expression of Lpp(C21G) via a σE-dependent small-regulatory RNA (sRNA), MicL-S. In contrast, restoration of growth via fis deletion is only partially dependent on the MicL-S pathway; deletion of fis also rescues Lpp(C21G) growth arrest in cells lacking physiological levels of phosphatidylglycerol (PG) and cardiolipin (CL), independently of MicL-S. Our results suggest a close link between the physiological state of the bacterial cell membrane and DnaA- and Fis-dependent growth.